SOCIALIZATION OF MIGRATION SERVICES AT CLASS II IMMIGRATION OFFICE TPI BELAKANG PADANG - Virra Wirdhiningsih; Atthariq Nur Aminuddin (Jurnal Abdimas Imigrasi, 2022)
This paper discusses the implementation of Field Work Practices (PKL) at the TPI Class II Immigration Office behind the desert. The street vendors succeeded in providing opportunities for cadets to observe and understand the mechanisms and constraints in various sections of the Immigration Office. Problems identified include the efficiency of passport collection, the effectiveness of passport applicant complaints, violations of residence permits for foreigners, and procurement of goods for the Immigration Office. However, through cooperation between officers, these problems can be overcome, so that the best service is still provided to Indonesian citizens and foreigners in Indonesia.